Deubiquitylating enzyme USP9x regulates hippo pathway activity by controlling angiomotin protein turnover - Nguyen, H.; Andrejeva, D.; Gupta, R.; Choudhary, C.; Hong, X.; Eichhorn, Pieter; Loya, A.; Cohen, S. (NATURE PUBLISHING GROUP, 2016)
The Hippo pathway has been identified as a key barrier for tumorigenesis, acting through downregulation of YAP/TAZ activity. Elevated YAP/TAZ activity has been documented in many human cancers. Ubiquitylation has been shown to play a key role in regulating YAP/TAZ activity through downregulation of a number of Hippo pathway components. Several ubiquitin ligase complexes have been implicated in this process, however, little is known about the deubiquitylating enzymes that counteract these activities to regulate YAP/TAZ. Here we identify the deubiquitylating enzyme USP9x as a regulator of YAP/TAZ activity. We demonstrate that USPx regulates ubiquitin-mediated turnover of the YAP inhibitor, Angiomotin. USP9x acts to deubiquitylate Angiomotin at lysine 496, resulting in stabilization of Angiomotin and lower YAP/TAZ activity. USP9x mRNA levels were reduced in several cancers. Clinically, USP9x mRNA levels were reduced in several cancers with low USPx expression correlating with poor prognosis in renal clear cell carcinoma. Our data indicate that USP9x may be a useful biomarker for renal clear cell carcinoma.